2015
DOI: 10.1371/journal.pone.0117645
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Description of Eye Defects in the Zebrafish Pax6b Mutant, sunrise, Reveals a Pax6b-Dependent Genetic Network in the Developing Anterior Chamber

Abstract: The cornea is a central component of the camera eye of vertebrates and even slight corneal disturbances severely affect vision. The transcription factor PAX6 is required for normal eye development, namely the proper separation of the lens from the developing cornea and the formation of the iris and anterior chamber. Human PAX6 mutations are associated with severe ocular disorders such as aniridia, Peters anomaly and chronic limbal stem cell insufficiency. To develop the zebrafish as a model for corneal disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 63 publications
3
39
0
Order By: Relevance
“…Hybridisation was performed at 65 °C in the presence of 1 mM EDTA to block endogenous alkaline phosphatase activity. After colour development with bromo-4-chloro-3-indolyl phosphate (BCIP, Roche) and nitroblue tetrazolium chloride (NBT, Roche), embryos were embedded into epoxy resins and 5 μm thick transverse sections were cut at the level of trunk as described 44 .…”
Section: Methodsmentioning
confidence: 99%
“…Hybridisation was performed at 65 °C in the presence of 1 mM EDTA to block endogenous alkaline phosphatase activity. After colour development with bromo-4-chloro-3-indolyl phosphate (BCIP, Roche) and nitroblue tetrazolium chloride (NBT, Roche), embryos were embedded into epoxy resins and 5 μm thick transverse sections were cut at the level of trunk as described 44 .…”
Section: Methodsmentioning
confidence: 99%
“…Mutations of PITX2 (Zhao et al, ) and FOXC1 (Pasutto et al , ) have also been implicated in up to 63% of patients with Axenfeld–Rieger syndrome (Reis et al , ), which is characterized by abnormal corneal endothelium development and retention of primordial endothelial tissue across the iris surface and anterior chamber angle (Shields, ). Similar corneal endothelial developmental anomalies may be induced in animal models, such as zebrafish PAX6 orthologue mutants (Takamiya et al , ) and mice whose PITX2 and FOXC1 gene expression patterns have been modified (Berry et al , ). Conversely, healthy corneal endothelial cells from humans and various animal species have also been shown to exhibit similar genotypic and phenotypic traits.…”
Section: Validity Of Interspecies Comparisonsmentioning
confidence: 88%
“…A number of chromosomal abnormalities and specific genetic mutations have been associated with Peters anomaly as well [8, 9, 10]. In a recent article, Takamiya et al [11] concluded that human PAX6 mutations are linked to some ocular diseases, one of which was Peters anomaly. In addition, genetic mutations in beta 1,3-galactosyltransferase-like gene (B3GALTL) were proposed to cause Peters plus syndrome [12], while microdeletions of 8q21.11 have demonstrated variable manifestations of Peters anomaly [13].…”
Section: Discussionmentioning
confidence: 99%